2021
DOI: 10.15549/jeecar.v8i4.810
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the interrelations between country risk, economic growth and good governance: The case of the Visegrád four

Abstract: nvestors assess the environment and the level of risk before they invest in a specific region or country. Several country risk indexes have been developed since the beginning of the 1990s, using risk factors such as politics, the economy and sovereign risk factors. This study aims to determine the relationships between the country risk index, economic performance and good governance. The study implemented a quantitative research methodology with panel data, focusing on the four Visegrad countries, using time-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…They found that the level of country risk, as measured by the PRS group (also used in this study as a proxy for country risk), significantly impacts domestic and FDI. Similar results were estimated by Meyer (2021) in an assessment of the Visegrad countries. Meyer and Mothibi (2021) investigated the impact of risk rating agencies' decisions on economic growth and domestic investment in South Africa from 1994 to 2020.…”
Section: Literature Reviewsupporting
confidence: 88%
“…They found that the level of country risk, as measured by the PRS group (also used in this study as a proxy for country risk), significantly impacts domestic and FDI. Similar results were estimated by Meyer (2021) in an assessment of the Visegrad countries. Meyer and Mothibi (2021) investigated the impact of risk rating agencies' decisions on economic growth and domestic investment in South Africa from 1994 to 2020.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Academics, decision-makers, and leaders in the tourist industry are becoming increasingly interested in how locals think about the growth of the tourism industry. There are questions concerning the economic viability of tourism and its costs and advantages for the host society (Afthanorhan et al, 2017;Meyer, 2021). One of the post-industrial age's new ideas is community participation, which comes from the political sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It improves firm performance and competitiveness and is a royal path to business greatness (Sakilu & Kibret, 2015). Effective planning and management are also good governance (Meyer, 2021). Corporate governance is concerned with the ethical standards of businesses (Can Inci, 2020).…”
Section: Introductionmentioning
confidence: 99%